2020
DOI: 10.1111/add.15216
|View full text |Cite
|
Sign up to set email alerts
|

Opioid overdose experiences in a sample of US adolescents and young adults: a thematic analysis

Abstract: Background and Aims Opioid overdose deaths among adolescents and young adults have risen sharply in the United States over recent decades. This study aimed to explore the nature of adolescent and young adult perspectives on overdose experiences. Design This study involved thematic analysis of interviews undertaken as part of a mixed‐methods, randomized trial of extended release naltrexone (XR‐NTX) versus treatment‐as‐usual (TAU) for adolescents and young adults (aged 15–21 years) with opioid use disorder (OUD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…The 113% increase in YLL to unintentional overdose is contrasted to the change in YLL to intentional overdose, which remained stable from 2019 to 2020. However, it can often be difficult to distinguish whether an overdose is intentional or unintentional [30]. Adolescent-aged participants in a 2020 study detailed their experiences with opioid-related overdose and described the desire to reach a state of maximum high without the intention of overdosing to the point of dying [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 113% increase in YLL to unintentional overdose is contrasted to the change in YLL to intentional overdose, which remained stable from 2019 to 2020. However, it can often be difficult to distinguish whether an overdose is intentional or unintentional [30]. Adolescent-aged participants in a 2020 study detailed their experiences with opioid-related overdose and described the desire to reach a state of maximum high without the intention of overdosing to the point of dying [30].…”
Section: Discussionmentioning
confidence: 99%
“…However, it can often be difficult to distinguish whether an overdose is intentional or unintentional [30]. Adolescent-aged participants in a 2020 study detailed their experiences with opioid-related overdose and described the desire to reach a state of maximum high without the intention of overdosing to the point of dying [30]. Therefore, although the data collected show a significant contrast between YLL to unintentional and intentional overdoses, the difference between the two might be smaller than what is shown due to the reality that intentionality of an overdose is more of a spectrum than a binary construct [30].…”
Section: Discussionmentioning
confidence: 99%
“…Future research should explore these notable characteristics and other candidates in larger samples of young adults, and should utilize assessments and measurements specifically designed to address hypotheses related to developmental vulnerability. Such variables could include measures of impulsiveness, emotion regulation, excitement-seeking, 24 perceptions of harm, 28 further exploration of sources of motivation, 19 therapeutic alliance and treatment engagement, 7,8,10 perceptions and use of social supports, 11,12 deviant peer affiliations, psychiatric comorbidity, 25 and parental and other caregiver status. An area of particular interest would be a more detailed exploration of cognitive differences in relation to treatment outcomes, especially in executive function, [29][30][31][32] since the developmental literature clearly points to immaturity in youth, some studies have found deficits in youth SUD populations, [33][34][35] and some have shown associations with poorer treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This is a critical developmental period, and an age period when substance use initiation is at its peak [ 13 16 ]. Research into perceptions of substance use suggest that youth view it as acceptable and with low risks; and thus, youth may be less likely to recognize the harms associated with substance use and when support may be needed [ 15 , 17 19 ]. It is also widely known that earlier initiation of opioid use increases the risk of developing OUD and other longer-term health and social harms (e.g.…”
Section: Introductionmentioning
confidence: 99%